COVID-19 pandemic and environmental protection: Imperatives for environmental law and management in Nigeria - Ekpoudo, Anthony; Ebu, Alex Abang; Aniashie, Akpanke Shishiitileugiang; Edet, Okpong Denis; Eteng, Ekpe Wekeekayo (Edelweiss Applied Science and Technology, 2024)
Across the global community, many countries have been ravaged by the challenge of the COVID-19 pandemic. Nigeria is no exception. Since the country recorded its first index case in February 2020, the number of cases and fatalities has been on the increase. Although the authorities in Nigeria have endeavoured to adopt some meaningful response to the pandemic, with a fragile healthcare system, the pressure posed by this issue is enormous and the matter has persisted. COVID-19 is certainly a zoonotic or environmentally related scourge. In this work, the environmental aspect of the pandemic has been traced and their consequences highlighted. The study also considers the responses to the problem and from the environmental law perspective examines the regulations concerning these kinds of diseases. It is opined that the effective management of the environment by adherence to agreements, laws, and policies, investment in environmental restoration and new technologies, and general reorientation of citizens towards the exploitation and use of environmental resources are better approaches to checking the emergence of this kind of problem in future and generally sustaining a green environment.